2015
DOI: 10.1111/codi.12930
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic excision of synchronous large bowel polyps in the presence of colorectal carcinoma: is the fear of malignant cell implantation justified? A systematic review of the literature

Abstract: The topic of colorectal cancer seeding following endoscopic procedures has received little attention. This review suggests that in the presence of a proximal colonic carcinoma there is a negligible risk of malignant implantation if a more distal polyp is endoscopically excised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…These findings are also consistent with the systematic review by Sheel et al [ 9 ]. In this systematic review, the only identified literature that studied human subjects was an isolated case report [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are also consistent with the systematic review by Sheel et al [ 9 ]. In this systematic review, the only identified literature that studied human subjects was an isolated case report [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…In turn, such an approach subjects patients to a further endoscopic procedure that could have been avoided had a polypectomy been performed during the initial diagnostic colonoscopy. This formed the premise of an earlier systemic review by Sheel et al [ 9 ]. In this review, articles were included if they described human or mammalian models related to colorectal cancer cell implantation on normal and damaged colonic mucosa, such as polypectomy sites.…”
Section: Introductionmentioning
confidence: 87%
“…13,14 Moreover, the experiments conducted do not exclude possibilities of tumor transmission other than working channel contamination, such as exfoliation of cancer cells passively being taken up into biopsied or polypectomy site tissue. 7 Studies on tumor regrowth based on exfoliated cells performed in rats showed that colon cancer cells have the ability to regrow on damaged mucosa in a minority of cases, whereas an intact mucosa was seen to be completely resistant. 15 This suggests that some extent of mucosal injury is necessary for impaction of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Yet, the risk of spontaneous tumor seeding, that is, implantation of tumor cells in damaged mucosa when polypectomy or biopsy is performed in the presence of CRC elsewhere in the colorectum, is estimated to be low. 7 However, the possibility of mechanical tumor seeding during colonoscopy, involving iatrogenic implantation of tumor cells in damaged mucosa, has never been explored.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Second, filiform polyposis was formed by an inflammation of colon diverticulitis; then the obstruction caused an implantation of sigmoid colon adenocarcinoma to erosive mucosa of filiform polyposis. Colon adenocarcinoma rarely develops in the defective part of mucosa [18]. Third, collision between sigmoid colon adenocarcinoma and the malignant transformation of filiform polyposis possibly occurred.…”
Section: Discussionmentioning
confidence: 99%